La socialisation sexuée au stade de la prime enfance : des rapports de force ? - Cécile Albert (Éducation et Socialisation)
Our study constitutes a contribution to the investigation into gendered social relations at the stage of early childhood. What are their characteristics? What impact do they have on social interactions? By means of an experiment using standardized games, the impact of gendered games upon gendered behavior and gendered interaction was measured. These regular observations were then compared to interviews with professional experts on early childhood. The interest of such research lies in the analysis of the gendering process on the basis of real-life observation. In particular it raises the question of how to define a gendered ego at such an age, while at the same time underlining the potential problems it raises for young boys and for their construction of an identity of their own when confronted with instances of female ascendancy. This leads to the adoption of a critical position with regard to the stereotyped view of the reproduction of relations of dominance and requires further attention to be paid to this topic. This raises problems too for the science of education, the challenge being to define the development of the autonomy and equality of the sexes from very early childhood.